Effects of the in ovo injection of an Escherichia coli vaccine on the hatchability and subsequent early post hatch characteristics of commercial layer chicks - K.E.C. Elliott; L.L. Lindsey; J.D. Evans; S.A. Leigh; K.J. Robinson; S.A. Fatemi; A. Mousstaaid; P.D. Gerard; J. L Purswell; E.D. Peebles (Poultry Science)
In the commercial table egg industry, avian pathogenic E. coli (APEC) can lead to significant economic loss and bird mortality. The Poulvac E. coli vaccine (PECV) (Zoetis, Parsippany, NJ) may be administered to poultry post hatch via coarse spray or in drinking water to protect against APEC infections. The purpose of this experiment was to in ovo vaccinate commercial layers with various doses of the PECV to evaluate hatchability and post hatch development of the chicks through 21 d of age. Eggs were either non-injected or vaccinated at 18 d of incubation with a diluent-injected control or one of the PECV treatments which included a full dose (2.65 × 107 E. coli CFU/egg) or dilutions of the full dose to produce 2.65 × 105, 2.65 × 103, or 2.65 × 101 CFU/egg. Mean hatch of injected eggs was significantly (P < 0.0001) affected by treatment, with all the PECV treatments significantly decreasing hatch. Mean chick BW was determined on d of hatch and at 1, 2, and 3 wk post hatch, and mean chick length was determined at 3 wk post hatch. Chick BW was significantly (all P < 0.0001) different between treatments at 1, 2, and 3 wk of age, with the chicks that had received diluent alone having the highest BW, and the chicks that had received the full dose having the lowest BW. Chick length was significantly (P = 0.045) different between treatments, with the chicks in the full dose treatment having a shorter body length than the chicks in the 2 control groups. Cumulative mortality from 0 to 21 d of growout was 5.41% in the full dose treatment, whereas no mortalities were observed in the other treatment groups. While layer chicken embryos were able to survive to 3 wk post hatch after having received the PECV by in ovo injection, the full dose of the vaccine increased cumulative chick mortality and decreased chick BW through 3 wk post hatch.